KEDISIPLINAN BELAJAR SISWA BERPRESTASI SEKOLAH DASAR NEGERI 13/1 RENGAS CONDONG MUARA BULIAN - Pamela, Issaura Sherly; Dewi, Diyah Fitriana; Vandera, Dea (Lentera: Jurnal Ilmiah Kependidikan, 2019)
The purpose of this research is to determine the discipline of learning of high achieving students in SD 13/1 Rengas Condong Muara Bulian. This research was conducted in odd semester 2019/2020. This research is motivated by the existence of students applying disciplinary life in the school environment, students successfully applying discipline such as arriving on time, this study uses a qualitative approach to the type of descriptive research, data collection is done by observation, interviews, and documentation in the form of learning activities in the classroom. Researchers directly conducted interviews with class teachers and students concerned. The results of the study To helping disciplinary success there needs to be a good cooperative relationship between the school principal, class teacher, parents and school committee in SD Negeri 13/1 Rengas Condong Muara Bulian.